A Study on the Efficiency of Sediment Basin - Andy, Kavines; Adnan, Mohd Shalahuddin (Recent Trends in Civil Engineering and Built Environment, 2023)
A healthy ecosystem, which include soil, water, and plant life is critical for human survival and wellbeing. However, the earth eco-system has been disrupted in the past as a result of excessive exploration of nature in order to meet demand caused by urbanization. As a result of the development, soil on land surfaces was exposed to rain directly causes sedimentation. The determination to minimize sediment is important as we can stop it. This study is introducing three design of sediment basin that could minimize sedimentation problem. Parameter such as Total suspended solids is focused in this study. Sediment basin is developed by using baffle and vegetation. Concentration water which have 598.0 mg/L of TSS value turn into 33.3 mg/L after flow through physical basin.